Process analysis of procalcitonin monitoring within community hospitals. (1st April 2020) - Peña, Kelsey; Cooper, Mandelin; Greer, Nickie; Elders, Ty; Septimus, Edward
Abstract: Purpose: Monitoring of procalcitonin (PCT) levels may support appropriate antibiotic discontinuation. The purpose of this study was to determine the current state of PCT monitoring at community hospitals across the United States. Methods: Data from adult patients who were admitted to community hospitals affiliated with a large healthcare system between August 1, 2016, and July 31, 2017, and who received antibiotics were evaluated for the number of PCT levels drawn and the timing between multiple levels. Data from eligible patients were evaluated for the discontinuation of antibiotics after meeting prespecified PCT thresholds for discontinuation of therapy, namely, a PCT measurement of <0.5 μg/L or a decrease of ≥80% from a previous peak value. Results: PCT levels were evaluated for 103, 913 patient data sets collected from 136 hospitals. Of these, 70% of the data sets showed a single PCT level drawn, and approximately 30% (30, 887) of the data sets showed multiple levels drawn. The first PCT measurement was drawn within 36 hours of antibiotic initiation in 96% of the patients. Of those with multiple levels, 23% (7, 089) had levels drawn 24 to 72 hours apart. A small proportion (20% [6, 127]) of the patients with multiple levels were eligible for evaluation of appropriate antibiotic discontinuation. Of these, 1, 973 (32.2%) patients had antibiotics discontinued within 36 hours of meeting the prespecified PCT thresholds; these patients had a mean duration of antibiotic therapy of 6.1 days with a median of 4.7. Conclusion: Additional standardization of ongoing PCT monitoring and education regarding the appropriate discontinuation of antibiotics when thresholds are reached could aid in the use of this biomarker in support of antibiotic and laboratory stewardship.